Dynamic high-frequency dependence structure of Chinese agricultural commodity futures based on the semi-parametric copula - Xiao, Renhong (Frontiers in Applied Mathematics and Statistics, 2023)
This paper investigates the dynamic high-frequency dependence structure of Chinese four major agricultural commodity futures by utilizing a semi-parametric copula-based multivariate model with 5-minute high-frequency trading data. The empirical results show that the daily dependence between the agricultural commodity futures is time-varying and slightly asymmetric, and that this dependence and its asymmetry are more pronounced during the world food crisis (2007-2008) and the global financial crisis (2008-2011). Furthermore, the intraday dependence structure exhibits a lopsided inverted U-shaped pattern with relatively lower dependence level around the opening and closing time, and a peak around the mid-trading day. This paper contributes the literatures by revealing the three typical dynamic characteristics of dependence structure of Chinese agricultural commodity futures market, and developing the semi-parametric copula model with high-frequency data.